KAJIAN KELEMBAGAAN AGRIBISNIS DALAM MENDUKUNG PENGEMBANGAN SISTEM USAHA PERTANIAN BERBASIS AGROEKOSISTEM - SADIKIN, IKIN; NUR SUHAETI, RITA; SURADISTRA, KEDI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 1 Februari 2004, 2012)
Research on agricultural institution with agribusiness orientation has not yet been given much attention. Yet, farmers obtain information on technology, market and processing techniques through the existing institutional roles, either in forms of organization, norms or community figures. The effort to accelerate the flow of agricultural inputs, process of technology transfer, and other production factors is a collective activity depicted in institutional network in local agricultural activities. A participatory observation using Rapid Appraisal of Agriculture Knowledge Systems (RAAKS) methodology concludes that the present primordial institution in each production segment process positive potential to develop and that shared objective is recognized as the starting point to develop an institution. Moreover, size of organization, membership status and institutional orientation also play important roles in the development of an institution, minimum commercial size, and policy on managerial development.
Keywords: Institution, Organization, Norms, RAAKS.